Salivary Microbiota Shifts under Sustained Consumption of Oolong Tea in Healthy Adults - Liu, Zhibin (Nutrients, 2020)
Tea is the most widely consumed beverages next to water, however little is known about the influence of sustained tea consumption on the oral bacteria of healthy adults. In this study, three oral healthy adults were recruited and instructed to consume 1.0 L of oolong tea infusions (total polyphenol content, 2.83 g/L) daily, for eight weeks. Salivary microbiota pre-, peri-, and post-treatment were fully compared by high-throughput 16S rRNA sequencing and multivariate statistical analysis. It was revealed that oolong tea consumption reduced salivary bacterial diversity and the population of some oral disease related bacteria, such as Streptococcus sp., Prevotella nanceiensis, Fusobacterium periodonticum, Alloprevotella rava, and Prevotella elaninogenica. Moreover, via correlation network and Venn diagram analyses, seven bacterial taxa, including Streptococcus sp. (OTU_1), Ruminococcaceae sp. (OTU_33), Haemophilus sp. (OTU_696), Veillonella spp. (OTU_133 and OTU_23), Actinomyces odontolyticus (OTU_42), and Gemella haemolysans (OTU_6), were significantly altered after oolong tea consumption, and presented robust strong connections (|r| > 0.9 and p < 0.05) with other oral microbiota. These results suggest sustained oolong tea consumption would modulate salivary microbiota and generate potential oral pathogen preventative benefits. Additionally, diverse responses to oolong tea consumption among subjects were also noticed.